Financial management and financial well-being of newly married couples: Practices and knowledge / Leylawati Joremi - Leylawati , Joremi (2020)
Prudent financial management is a critical factor to achieve better financial well-being. The failure of many individuals in managing their finances, resulting in bankruptcy, distress and divorce. Recognizing the importance of financial management practices as a roadmap towards future financial well-being, a study on young and newly married couples is imperative. This study intends to attain a profound understanding of financial management practices among urban Malays young couples. This study also deliberates the understanding of these couples on financial well-being. It takes the phenomenological approach and analyses qualitative data collected through a series of in-depth interviews. The interviews explore the actual experience of five couples in managing day-to-day household finances in terms of the resource management system, distribution of household financial responsibilities, expenditure control, savings and investment preferences, enabling richer data to be obtained. The study also sought to uncover the couples’ understanding of financial well-being. Several financial management practices themes emerged from the data. The study indicated that managing finances is a process which needs to be implemented at a young age. Therefore, the findings suggested that families form an effective way of controlling the flow of money as soon as they enter into marriage. In fact, activities performed by these couples were driven by the state of affairs and desire to achieve financial independence. Therefore, the wisdom in managing finances at present and the prudently crafted initiative steps for their long-term planning are seen as a roadmap towards achieving a higher level of financial well-being in the future. The financial viability is realized with the idea of controlling spending activities, thrifty, vigilant and diligently making this process a regular routine. In addition, adherence to religious teachings is also an important pillar in balancing the well-being of life on a wider concept.